Decreased incremental shuttle walk test distance characterized by fibrocavitary lesions in non-tuberculous mycobacterial pulmonary disease. Issue 4 (3rd April 2022) - Ono, Kazuki; Tabusadani, Mitsuru; Yamane, Kazumasa; Takao, Satoshi; Mori, Kosuke; Matsumura, Yusuke; Kuroyama, Yuku; Kawahara, Kazuma; Omatsu, Shunya; Furuuchi, Koji; Fujiwara, Keiji; Morimoto, Kozo; et al.
ABSTRACT: Background: Patients with non-tuberculous mycobacterial pulmonary disease (NTM-PD) have impaired exercise capacity, but the underlying factors are unknown. We investigated the characteristics of patients with NTM-PD and impaired exercise capacity. Methods: In total, 149 patients with NTM-PD participated in this study. Patients completed the incremental shuttle walk test (ISWT) to assess exercise capacity. Peripheral muscle strength and pulmonary function were also assessed. Radiological findings were classified into three phenotypes: non-cavitary nodular bronchiectatic (NC-NB) form, cavitary nodular bronchiectatic form, and fibrocavitary (FC) form. Results: The median ISWT distance (ISWD) and %ISWD were 450 meters and 88%. Participants were classified into three groups according to %ISWD, with %ISWD <60% as the severely decreased group, 60%-80% as the moderately decreased group, and >80% as the normal or mildly decreased group. In a comparison of %ISWD among phenotypes, FC form had significantly lower %ISWD than those with NC-NB form. In the severely decreased group, peripheral muscle strength and pulmonary function were significantly lower than the other two groups. From a radiological standpoint, significantly more patients had FC form in the group with severely decreased %ISWD. Conclusions: Decreased ISWD is characterized by a deterioration in physical function and the presence of FC lesions in NTM-PD.